Effect of Rapid Molecular Diagnostic Testing and Antimicrobial Stewardship on Antimicrobial Therapy of Respiratory Infections. (4th October 2017) - File, Thomas M; Politis, Paula; Tan, Michael J; Kallstrom, George
Abstract: Background: Rapid molecular methods have created new opportunities for the clinical microbiology laboratory to affect patient care in the areas of initial diagnosis and therapy. Rapid diagnostic tests provide collaborative opportunities for antimicrobial stewardship Teams (AST) to improve patient outcomes and decrease antimicrobial use. In January of 2017 our institution initiated use of a FDA approved multiplex polymerase chain reaction (PCR) Respiratory Panel. The objective of this evaluation was to assess the clinical impact along with procalcitonin (PCT) on quality of patient care when used in conjunction with antimicrobial stewardship. Methods: Molecular testing was performed using the BioFire FilmArray® Respiratory Panel [RP] (BioMerieux). The medical staff was encouraged to order an Influenza/RSV PCR test prior to ordering the full RP. The results of RP and PCT were available the same day as ordered. AST recommended the RP as part of its intervention on several patients and provided advice based on results. Results: From January-April the results of 81 tests for the respiratory panel were evaluated. Of these 30 were positive (+) for virus (most common-Human Metapneumovirus [HMV]-13, Coronavirus-7). PCT (ng/mL) results were available on 69. Most common final diagnosis: Pneumonia-31; AECOPD-16. Effect on duration of antimicrobial therapy (ABX) and hospital length of stay (LOS): Conclusion: The results of the RP led to a decrease in ABX duration, which was most profound in the patients for whom AST intervened. LOS was also reduced. Utilization of RP and PCT facilitated better ABX use. Disclosures: T. M. File Jr., BioMerieux: Scientific Advisor, Consulting fee